2011
DOI: 10.1177/0145482x1110500402
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technology for Students with Visual Impairments: Challenges and Needs in Teachers’ Preparation Programs and Practice

Abstract: This article reports on a survey of 165 teachers of students with visual impairments in Texas to examine their perceptions of their knowledge of assistive technology. The results showed that they had significant deficits in knowledge in 55 (74.32%) of the 74 assistive technology competencies that were examined and that 57.5% of them lacked adequate confidence about teaching assistive technology to students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 11 publications
3
54
0
2
Order By: Relevance
“…Before assistive technology devices can be incorporated in the learning, however, teachers need to determine how useful assistive technology is in the context of instruction and its potential impact on student outcomes (Parette et al , ). At the same time, while teachers of students with visual impairments (TVIs) are key resource persons for support (Presley and D’Andrea, ), reports continue to indicate assistive technology proficiency and pertinency of training received in light of rapid technology advancements as ongoing pressures in the TVIs successful role in providing assistive technology support (Zhou et al , ; Morash and Siu, ). Guidance in assistive technology support for TVIs is necessary to mitigate such pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Before assistive technology devices can be incorporated in the learning, however, teachers need to determine how useful assistive technology is in the context of instruction and its potential impact on student outcomes (Parette et al , ). At the same time, while teachers of students with visual impairments (TVIs) are key resource persons for support (Presley and D’Andrea, ), reports continue to indicate assistive technology proficiency and pertinency of training received in light of rapid technology advancements as ongoing pressures in the TVIs successful role in providing assistive technology support (Zhou et al , ; Morash and Siu, ). Guidance in assistive technology support for TVIs is necessary to mitigate such pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Children living with visual impairments are increasingly educated in mainstream schools alongside their sighted peers, rather than in special schools [76]. However, despite being included with their sighted peers, recent research has identified persistent issues with participation [88,94], reduced opportunities for collaborative learning and social engagement [6,36] and potential for isolation [60]. These challenges have been attributed in part to the technical support that children with VIs receive in mainstream schools.…”
Section: Accessibility and Inclusionmentioning
confidence: 99%
“…Despite the fact that regular education teachers are nonspecialists in the field of visual impairment, they must have sufficient knowledge in order to provide visually impaired students with an effective school education through participation in all activities as their sighted peers (Gasparetto 2001). In fact, it is important to assess the perceptions of all teachers involved in the educational process of students with visual impairments (Alves et al 2009;Zhou et al 2011). In this context, this study intends to analyse the perceptions of teachers who taught visually impaired students in the 2012/2013 school year in middle school and secondary school education, in Portuguese reference schools for the education of blind and partially sighted students, of their knowledge, teaching and training in the area of ICT, as well as the use of ICT by these learners.…”
Section: The Studymentioning
confidence: 99%
“…Holmes et al (2008) consider that teachers of visually impaired students need to understand and implement the use of the latest assistive technology. Despite the almost non-existent research conducted in Portugal in the field of visual impairment, international studies indicate that teachers of visually impaired students do not have enough training on technologies that are relevant to this area (Abner and Lahm 2002;Kapperman et al 2002;Smith and Kelley 2007;Zhou et al 2011). This lack of specific training is "more severe for teachers in the regular classroom" (Papadopoulos and Goudiras 2005, p. 75), than for special education teachers.…”
Section: Introductionmentioning
confidence: 99%